2019
DOI: 10.1055/s-0039-1693728
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin Reduces Necrotizing Enterocolitis Severity by Upregulating Intestinal Epithelial Proliferation

Abstract: Introduction Necrotizing enterocolitis (NEC) is a devastating intestinal illness in premature infants characterized by severe intestinal inflammation. Despite medical interventions, NEC mortality remains alarmingly high, which necessitates improved therapies. Lactoferrin is among the most abundant proteins in human milk and has important immunomodulatory functions. While previous studies have indicated protective effects of lactoferrin against neonatal sepsis and NEC, the underlying mechanism remains unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
(24 reference statements)
2
10
0
Order By: Relevance
“…Third, it is challenging to determine the optimal therapeutic regimen (dose, frequency, timing). Even though dose is of clear importance for the therapeutic effect [36,101], most animal studies only test a single dose and frequency of administration and it is therefore unclear how the dose and administration regimen used in animal studies should be translated to the human neonate. Of note, the optimal dose for the human neonate may be very well dependent on individual baseline levels, e.g., an infant with baseline deficit of a specific nutritional component may benefit from a higher dosage than an infant with baseline values within the normal range.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Third, it is challenging to determine the optimal therapeutic regimen (dose, frequency, timing). Even though dose is of clear importance for the therapeutic effect [36,101], most animal studies only test a single dose and frequency of administration and it is therefore unclear how the dose and administration regimen used in animal studies should be translated to the human neonate. Of note, the optimal dose for the human neonate may be very well dependent on individual baseline levels, e.g., an infant with baseline deficit of a specific nutritional component may benefit from a higher dosage than an infant with baseline values within the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…These detrimental effects are likely caused by the high dose of the lactoferrin used, as in in vitro experiments with cultured intestinal epithelial cells a high dose, but not lower doses, of bovine lactoferrin upregulated the expression of pro-apoptotic proteins and HIF1α signaling pathway proteins and downregulated that of anti-apoptotic proteins and proteins related to cell proliferation [36]. In another study using a mouse model of NEC, enteral recombinant lactoferrin administration (6 g/L) prevented a NEC protocol induced decrease in Ki67 immunoreactivity, preserved beta-catenin immunoreactivity and restored LGR5 mRNA levels in the distal ileum [101]. Together, these studies demonstrate that the dose of the nutritional intervention studied is important and should be taken into account when designing a clinical trial.…”
Section: Protein or Amino Acid-based Feeding Interventionsmentioning
confidence: 97%
See 2 more Smart Citations
“…All these changes induced epithelial cell edema, apoptosis, and even death. It has been reported that the enhanced epithelial cell proliferation was associated with an alleviated NEC severity [ 38 ]. The proliferated epithelial cells contributed mostly in the repair of the impaired mucosa barrier, and we observed increased epithelial cell proliferation in NEC rats after PSB1115 administration.…”
Section: Discussionmentioning
confidence: 99%